The Reflection of Multilateral Environmental Agreements (MEAs) in the Barents Environmental Cooperation - Sellheim, Nikolas (Arctic Review on Law and Politics, 2012)
The Barents Euro-Arctic Region (BEAR) which was founded in 1993 is a dual-layered forum of cooperation between governments and regions in the Barents Region. It is based on the legally non-binding Kirkenes Declaration, whose overarching aim is to promote sustainable development in the region. To this end, the protection of the environment is to be included in all its activities. This article analyzes the inclusion of the concept of sustainable development in the cooperative structure of the BEAR based on the 1992 Rio Declaration and Agenda 21. Several selected Multilateral Environmental Agreements (MEA) are analyzed against the background of their reflection in the BEAR working procedures. In the case of some MEAs, different statuses of ratification in Russia and the Nordic Barents states aggravate their implementation in the BEAR context. Notwithstanding, the forum has developed different strategies which enable their successful application for the Barents Region.Keywords: Barents Euro-Arctic Region; Barents Environmental cooperation; Multilateral Environmental Agreements; Soft-law cooperation; Sustainable Development; Russian non-ratification.Citation: Arctic Review on Law and Politics, vol. 3, 2/2012 pp. 218–243. ISSN 1891-6252